2017
DOI: 10.1111/ppa.12766
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and pathogenicity assessment of Plectosphaerella species associated with stunting disease on tomato and pepper crops in Italy

Abstract: This study follows a survey carried out in 2012 and 2013 on tomato and pepper crops in the Foggia province (southern Italy), for morphological, molecular and pathogenicity analyses of Plectosphaerella fungi. The Plectosphaerella genus includes several species that are pathogens of horticultural plants. The survey identified tomato and pepper crops that showed abundant wilt, leaf yellowing, and discolouration and necrosis of roots, plus collar and stem symptoms. Different fungi including Plectosphaerella spp. w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 42 publications
3
18
0
1
Order By: Relevance
“…The observed dominant plant pathogens are common pathogens of potato, with a capability for saprophytic growth and infective spread to other hosts. Plectosphaerella cucumerina prevailed both in soil and root samples, which is in agreement with previous studies in Italy [49,50]. Although this pathogen causes wilting in potato [51], some studies have shown that P. cucumerina acts as a biocontrol agent against potato cyst nematodes [52].…”
Section: Dominant Taxasupporting
confidence: 91%
“…The observed dominant plant pathogens are common pathogens of potato, with a capability for saprophytic growth and infective spread to other hosts. Plectosphaerella cucumerina prevailed both in soil and root samples, which is in agreement with previous studies in Italy [49,50]. Although this pathogen causes wilting in potato [51], some studies have shown that P. cucumerina acts as a biocontrol agent against potato cyst nematodes [52].…”
Section: Dominant Taxasupporting
confidence: 91%
“…Alternaria and Fusarium have been largely reported in crop and natural seeds in great abundance ( Verma and White, 2019 )⁠. Additionally, beside the basidiomycetous yeast Vishniacozyma, all genus are also described as opportunist pathogenic taxa that are able to colonize plant tissues and seeds asymptomatically ( Thomma, 2003 ; Perelló and Larrán, 2013 ; Links et al., 2014 ; Raimondo and Carlucci, 2018 ; Henry et al., 2019 ). Possibly the core ASVs also have beneficial properties for plants and in particular for P. ramosa and it is unclear whether these taxa persist as ubiquitous endophytes due to the fungal dispersal strategy or as a plant strategy to supply beneficial microbes for a better offspring fitness ( Verma and White, 2019 )⁠.…”
Section: Discussionmentioning
confidence: 99%
“…Plectosphaerella populi: Patógeno de plantas hortícolas (50). Pleurostoma richardsiae: Patógeno causante de la enfermedad del tronco del vid (46).…”
Section: Hongos Patógenos Vegetales Y Humanosunclassified